Clinical Impact of Immune Checkpoint Inhibitor (ICI) Response, DNA Damage Repair (DDR) Gene Mutations and Immune-Cell Infiltration in Metastatic Melanoma Subtypes - Charlotte Andrieu; Niamh McNamee; Anne-Marie Larkin; Alanna Maguire; Roopika Menon; Judith Mueller-Eisert; Noel Horgan; Susan Kennedy; Giuseppe Gullo; John Crown; Naomi Walsh (Medical Sciences, 2022)
Molecular and histopathological analysis of melanoma subtypes has revealed distinct epidemiological, genetic, and clinical features. However, immunotherapy for advanced metastatic melanoma patients does not differ based on subtype. Response to immune checkpoint inhibitors (ICI) has been shown to vary, therefore, predictive biomarkers are needed in the design of precision treatments. Targeted sequencing and histopathological analysis (CD8 and CD20 immunohistochemistry) were performed on subtypes of metastatic melanoma (cutaneous melanoma (CM, n = 10); head and neck melanoma (HNM, n = 7); uveal melanoma (UM, n = 4); acral lentiginous melanoma (AM, n = 1) and mucosal melanoma (MM, n = 1) treated with ICI). Progression-free survival (PFS) was significantly associated with high CD8 expression (p = 0.025) and mutations in DNA damage repair (DDR) pathway genes (p = 0.012) in all subtypes but not with CD20 expression. Our study identified that immune cell infiltration and DDR gene mutations may have an impact in response to ICI treatment in metastatic melanoma but differs among subtypes. Therefore, a comprehensive understanding of the immune infiltration cells’ role and DDR gene mutations in metastatic melanoma may identify prognostic biomarkers.